A MULTI-LEVEL QUALITATIVE STUDY OF SENSITIVE-INTERVENTION STUNTING PROGRAM: FROM REGULATION TO IMPLEMENTATION ACTION - Tri Bayu Purnama; Syafran Arrazy; Nurhayati; Yulia Khairina Ashar; Grace Wangge (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: Stunting-sensitive intervention programs remain a public health issue due to multi-sectoral factors. These factors might affect the delay in the stunting reduction program, while the program should be elaborated with non-nutrition programs. Aims: to evaluate a stunting-sensitive program, which mapped the challenges in implementing intervention from regulation to an action basis.  Methods: This study used a qualitative study to describe a sensitive nutrition program by collecting data with several methods, both aspect in regulation and the action aspects of the stunting-sensitive intervention program. This study interviewed participants at multiple levels, including the regulator (The District of Health), the implementer (the Public Health Centre), and the target community, in relation to regional regulatory innovations on stunting prevalence. Results: This study found that the community is familiar with activities related to specific package programs and has limited information regarding sensitive interventions. Lack of coordination and collaboration among participants was observed. Public health parameters had not changed after innovations in regional regulations were implemented. Conclusion: Enhancing cadres' capacity, regulation innovation to action, and a program manager are needed to accelerate the sensitive intervention program. Keywords: collaboration-coordination, multilevel, qualitative, sensitive-intervention, stunting.